The biology, identification and management of Rhizoctonia pathogens - DANIEL P. ROBERTS; PRATIBHA SHARMA, PRASHANT P. JAMBHULKAR,DILIP K. LAKSHMAM (Indian Phytopathology, 2016)
The basidiomycetous soilborne fungus Rhizoctonia solani (sensu lato) is a pathogen of worldwide distribution and is known to attack economically important crops including cereals, vegetables, ornamentals, forest trees and turfgrasses. The broad group of Rhizoctonia also includes non-pathogenic, saprophytic, symbiotic and biocontrol isolates. Pathogenic groups exhibit selective host range, climatic adaptability and differential sensitivities to commonly used fungicides and biocontrol agents, thus pathogen identification becomes an essential prerequisite for effective disease management. Traditionally, isolates of R. solani are identified based on various morphological characters, the number of nuclei per cell and by hyphal anastomosis reactions with tester isolates, all of which are often unreliable methods for precise pathogen detection. Recent approaches utilizing genome fingerprinting with various molecular markers, and Internal Transcribed Spacers (ITS) sequencing have increased the speed, precision, and practicality of accurately identifying, grouping, and investigating population genetics of R. solani pathogens. Current investigations of various R. solani anastomosis groups (AGs) at the omics levels have opened up exciting possibilities for understanding their dynamic biological and pathogenic processes. This review focuses on current advancement and trends in research on molecular identification, genetic diversity, genomics, and management of this group of Rhizoctonia pathogens.